Komitmen Organisasi Dan Kinerja Karyawan pada Hotel Grandia Bandung - Dewi Kania; Suhendi (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
It is generally known that one of the most important elements of tourism is accommodation or hotel facilities. Hotel is a type of accommodation business that provides room facilities to stay with daily payment calculations and provides various types of other service facilities. In order to improve employee performance at Hotel Grandia Bandung, it needs to be improved through organizational commitment. This study aims to obtain a research model on organizational commitment and employee performance at Hotel Grandia Bandung. The method used is quantitative method with descriptive and verification analysis, survey and explanatory survey. Collecting data through observation and questionnaires to 43 employees of Hotel Grandia. Instrument testing with validity test, reliability test and normality test. Organizational commitment is formed with three dimensions, namely affective commitment, continuous commitment and normative commitment, while employee performance is formed with three dimensions, namely the dimensions of quality, quantity and timeliness. The results of the descriptive research show that organizational commitment is in the good to very good category, and employee performance is in the good to very good category. While the results of the verification research show that organizational commitment has a positive and significant effect on employee performance with an R2 (R Square) value of 0.401 = 40.1% and an error value of 0.591 or 59.1%.